Helicobacter pylori y su incidencia en la sintomatología gástrica en funcionarios policiales del cantón Babahoyo. Periodo septiembre 2017 a febrero 2018. - Medina Bran, Zulay Estefanía; Herman Arcenio Romero Ramírez (2018)
The present research work was carried out in the Babahoyo Canton Police Command, where a large number of police members live, where 100 people whose ages range from 20 to 60 years old were chosen, who presented eating disorders and symptoms of stomach inflammation. Due to this, we were able to choose a vulnerable population and due to the risk factors such as alcohol, tobacco, poor diet, they had symptoms of Helicobacter pylori. We took advantage of the results of the investigation as a necessary means of information to Babahoyo police officers through training to prevent the increase of cases of the bacteria. Using the inductive-deductive method in the present investigation, because it is a mixed method since induction and deduction are complemented in the process of gastric symptomatology that allows starting from the hypothesis proposed and that will be verified according to the progress of the research about the bacterium of Helicobacter Pylori in the gastric symptomatology in the police officers of the Babahoyo Canton.